Cytotoxic effects of methanolic extracts of Psidium guajava and Morinda citrifolia on human osteosarcoma SAOS-2 cells - Choo, Jie Ying (2015)
Cancer is a major health problem and causes significant morbidity and mortality. Bone cancer is an uncommon cancer that begins in a bone and it mostly occurs in children and teens. Cancer treatment by conventional medicine, surgery, chemotherapy and radiotherapy have been the primary approaches, but they are not always effective. The use of complementary alternative medicine (CAM) has grown rapidly in popularity both among the general population and among cancer patients. Therefore, we hypothesize that plant extracts exert antiproliferative effect on cancer cells. The objective of this study is to evaluate the antiproliferation effects on cancer cells using selected plant extracts. Results showed that Psidium guajava extracts showed cytotoxic effect on human Saos-2 cells, however, Morinda citrifolia extracts do not exhibit any inhibition on Saos-2 cells. P.guajava leaves have more cytotoxic effects than M.citrifolia leaves. Further study of P. guajava can be applied to determine the optimal concentration of a leaf extract for cancer treatment, while, M. citrifolia can be recommended for further study on wound healing effects.